Female Genital Mutilation and Cosmetic Surgery: Regulating Non-Therapeutic Body Modification - Sheldon, Sally (Bioethics, 1998)
In the UK, female genital mutilation is unlawful, not only when performed on minors, but also when performed on adult women. The aim of our paper is to examine several arguments which have been advanced in support of this ban and to assess whether they are sufficient to justify banning female genital mutilation for competent, consenting women. We proceed by comparing female genital mutilation, which is banned, with cosmetic surgery, towards which the law has taken a very permissive stance. We then examine the main arguments for the prohibition of the former, assessing in each case both (a) whether the argument succeeds in justifying the ban and, if so, (b) whether a parallel argument would not also support a ban on the latter. We focus on the following arguments. Female genital mutilation should be unlawful because: (1) no woman could validly consent to it; (2) it is an oppressive and sexist practice; (3) it involves the intentional infliction of injury; (4) it causes offence. Our view is that arguments (3) and (4) are unsound and that, although arguments (1) and (2) may be sound, they support not only a ban on female genital mutilation, but also one on (some types of) costmetic surgery. Hence, we conclude that the present legal situation in the UK is ethically unsustainable in one of the following ways. Either the ban on female genital mutilation is unjustified because arguments (1) and (2) are not in fact successful; or the law's permissive attitude towards cosmetic surgery is unjustified because arguments (1) and (2) are in fact successful and apply equally to female genital mutilation and (certain forms of) cosmetic surgery. The people of the countries where female genital mutilation is practised resent references to ‘barbaric practices imposed on women by male-dominated primitive societies’, especially when they look at the Western world and see women undergoing their own feminization rites intended to increase sexual desirability: medically dangerous forms of cosmetic plastic surgery, for instance …